2021
DOI: 10.3389/fphys.2021.738878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Training on Physical Fitness Among Athletes: A Systematic Review

Abstract: There is evidence that functional training is beneficial for the overall physical fitness of athletes. However, there is a lack of a systematic review focused on the effects of functional training on athletes' physical fitness. Thus, the aimed of the present review is to clarify the effects of functional training on physical fitness among athletes. In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) Statement guidelines, the systematic search of PubMed, SCOPUS, EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 49 publications
(246 reference statements)
4
27
0
Order By: Relevance
“…Recent publications include a number of systematic reviews of FT programs. However, previous review studies addressed the effect of FT on muscle strength, balance, mobility, activities of daily living in older adults ( Liu et al, 2014 ), strength, endurance, balance ( Wilke and Mohr, 2020 ), adult health ( McLaughlin et al, 2020 ), physical fitness components ( Xiao et al, 2021 ), and the risk of injury in athletes ( Chen et al, 2021 ). To the best of our knowledge, no research has assessed how FT interventions affect athletes’ performance in terms of sprinting, jumping, and functional movements, which may enhance sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications include a number of systematic reviews of FT programs. However, previous review studies addressed the effect of FT on muscle strength, balance, mobility, activities of daily living in older adults ( Liu et al, 2014 ), strength, endurance, balance ( Wilke and Mohr, 2020 ), adult health ( McLaughlin et al, 2020 ), physical fitness components ( Xiao et al, 2021 ), and the risk of injury in athletes ( Chen et al, 2021 ). To the best of our knowledge, no research has assessed how FT interventions affect athletes’ performance in terms of sprinting, jumping, and functional movements, which may enhance sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…This type of training increased muscle activation when compared to traditional training under stable condition through changes in the surface support. Previous studies well-indicated efficiency of FRT for physical fitness ( Feito et al, 2018 ; Xiao et al, 2021 ) and capabilities ( La Scala Teixeira et al, 2017 ). Nevertheless, the unknown if the FRT protocols would generate changes in arterial stiffness, and the effect of FRT with unstable condition on muscular fitness has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 84%
“…Nevertheless, the overall influence of FRT on age-associated arterial stiffness is poorly understood. Functional resistance training involves synchronized, multidimensional, and multiple joint movement modes to train muscles with dynamic exercises and continuous changes on unstable surfaces (e.g., BOSU ball, swish ball, and balance disc) for enhancing physical fitness ( Feito et al, 2018 ), and it has been applied to improve the physical condition and health of players and for the postoperative recovery of patients and young adults ( Kibele and Behm, 2009 ; Xiao et al, 2021 ). Additionally, FRT is the most promising method for promoting multisystemic adaptations because it uses resistance training not only for central body strength gains but also for multiple capabilities (e.g., coordination, agility, flexibility, and cardiorespiratory endurance; La Scala Teixeira et al, 2017 ; de Resende-Neto et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%